6.6k views
5 votes
A.
3(t+4)-2(2t+3)=-4

User NightRa
by
5.8k points

2 Answers

7 votes

Answer:

t = 10

Explanation:

Step 1: Use distributive property and expand your problem.

3t + 12 − 4t − 6 = −4

Step 2: Next, simplify 3t + 12 − 4t − 6 into −t + 6 - t + 6 − t + 6.

−t + 6 = −4

Step 3: Then you will have to regroup your terms.

6 − t = −4

Step 4: you then subtract 6 from both sides.

−t = −4 − 6

Step 5: Next, simplify −4 − 6 to get −10.

−t = −10

Step 6: Lastly, multiply both sides by −1 and you're done!

t = 10

User IAfanasov
by
4.9k points
6 votes

Answer:

t = 10

Explanation:

Distribute 3 into (t + 4) and also distribute -2 into (2t + 3)

We have

3 x t + 3 x4 -2 x 2t + -2 x 3

Positive negative gives negative. So the sign at the right side changes to negative

3t + 12 - 4t - 6 = -4

Rearrange the expression

3t - 4t + 12 - 6 = -4

-1t + 6 = -4

Subtract 6 from both sides

-1t + 6 - 6 = -4 - 6

-1t = -10

Divide both sides by -1

-1t /-1 = -10/-1

t = 10

User Faizan Younus
by
5.8k points